Identification of NSTE-ACS patients with totally occluded infarct-related artery: the role of the SAVE risk score in improved risk stratification - Sun, Biao; Liu, Hong; Ma, Lilan; Li, Tao; Shi, Jiaxin; Yang, Xiaodan; Ma, Guofei; Wu, Xinhua (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThe aim of this study is to investigate the clinical characteristics of non-ST-segment elevation acute coronary syndrome (NSTE-ACS) patients with totally occluded infarct-related artery (IRA-TOCA) and validate the novel SAVE risk score for early identification.MethodsThis retrospective study analyzed 185 consecutive NSTEMI patients undergoing coronary angiography, stratified into IRA-TOCA (n = 61) and IRA-non-TOCA (n = 124) groups. Baseline characteristics, angiographic findings, and post-percutaneous coronary intervention (PCI) biomarkers were compared. Risk stratification was performed using Global Registry of Acute Coronary Events (GRACE) and SAVE scores.ResultsIRA-TOCA patients exhibited significantly higher post-PCI cTnI levels (8.3 vs. 3.34 ng/mL, P = 0.001), indicating more severe myocardial injury. Multivariable analysis identified IRA-TOCA [odds ratio (OR): 3.64, 95% confidence interval (CI): 1.77–7.49] and elevated brain natriuretic peptide (BNP) (OR: 1.001, 95% CI: 1.000–1.002) as independent predictors of cTnI elevation. The SAVE score demonstrated superior discriminatory ability (sensitivity 73.8%, specificity 54.8%; P < 0.001) compared to the GRACE score (P = 0.384). The left circumflex artery was the most common occlusion site (47.5%).ConclusionIRA-TOCA represents a high-risk NSTE-ACS subtype with distinct biomarker profiles. The SAVE score enables early identification, potentially guiding timely revascularization.